Visualization of defects images during manual ultrasonic inspection of parts and units of the railway rolling stock - A. N. Kireev (Вестник Научно-исследовательского института железнодорожного транспорта)
The article suggests a method for visualizing internal defects of parts and units of rolling stock, which is performed by representing defects images on type B and C scans in automated and mechanized ultrasonic testing systems. Methods of defectometry for manual ultrasonic testing by the echo impulse method are considered. Author presents the mathematical apparatus and the algorithm for determining the defect type by a two-frequency defectometry method. A mathematical apparatus and an algorithm are proposed for determining the equivalent sizes of defects of various types, such as point volume and planar defects and extended volume and planar defects. First, the types of defects are determined by a two-frequency method, then using the obtained data and mathematical transformations they are formed and displayed in the output window of the B- and C-scans of the monitored section. Work on the formation of the image of defects is carried out automatically with the help of the NDTRT-14 software developed by the author. The presented methods of defectometry and the software product can be used for ultrasonic inspection of the parts of the carriage section of the rolling stock having a plane-parallel ultrasonic input surface and the bottom surface - treads of wheel-sets of the traction rolling stock (control of the main section from the inner side surface), solid-rolled wheels of cars and locomotives (wheels’ rim and hub control in the axial direction), rolled wheel centers of traction rolling stock (wheels’ rim and hub control in the axial direction), preforms of the driven and driving gears of the traction reducer (control in the axial direction). The software product was successfully introduced into the technological process of ultrasonic control of the elements of the carriage section of the mainline diesel locomotives in the Public Joint Stock Company "Luganskteplovoz".